Developing leadership in an MNC : A sales personnel’s perspective - Minkkinen, Liisa (My University, 2019)
The challenging and fast-paced business environment of modern-day business has led to ever increasing demands for flexibility and renewability from the organizations. In the centre of this change are sales personnel, whose work is especially affected by the changes in the market. To ensure competitive advantage, organizations need to acknowledge the importance of their employees’ skills and focus on leadership development. Increasing self-leadership across organization helps them to discover their core competences, improve information flow and boost agility. Furthermore, it leads to decentralized decision-making, which further facilitates flexibility. The research was conducted as an assignment from the Case Company and by researching sales personnel, the aim was to describe how organizational roles need to change, so the company can become more self-leading and execute effective and profit-oriented self-leadership in multinational environment. Also, the research aimed to identify how inspirational leadership can be used to support the change towards self-leadership. The study was conducted using qualitative research methods. The data was collected from eight semi structured interviews with sales personnel from the Case Company. They had been employed in the company for several years and thus, were able to reflect the changes in self-leadership, their roles and leadership styles. The study followed an abductive research approach and the data was analysed by identifying different themes and combining similar themes so, that they eventually constructed the success factors of employees’, leaders’ and organization’s roles in moving towards a self-leading organization. The results suggest that overall the organizational culture needs to become more trusting, and the hierarchy less centralized. This requires action from both the employees and supervisors. Employees are required to take more responsibility over competence and performance and have appropriate team work skills. Simultaneously, the supervisors need to give the employees possibilities to participate in decision-making and trust them to monitor their own performance.
Keywords: Leadership development, self-leadership, inspirational leadership; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business